Structure of the pre-60S ribosomal subunit with nuclear export factor Arx1 bound at the exit tunnel - Bradatsch, Bettina; Gnädig, Marén; Hurt, Ed (Nature structural & molecular biology, 2012)
Preribosomal particles evolve in the nucleus through transient interaction with biogenesis factors before export to the cytoplasm. Here, we report the architecture of the late pre-60S particle, purified from Saccharomyces cerevisiae, through Arx1, a nuclear export factor with structural homology to methionine aminopeptidases, or its binding partner Alb1. Cryo-EM reconstruction of the Arx1 particle at 11.9-Å resolution reveals regions of extra density on the pre-60S particle attributed to associated biogenesis factors, confirming the immature state of the nascent subunit. One of these densities could be unambiguously assigned to Arx1. Immunoelectron microscopy and UV cross-linking localize Arx1 close to the ribosomal exit tunnel, in direct contact with ES27, a highly dynamic eukaryotic rRNA expansion segment. The binding of Arx1 at the exit tunnel may position this export factor to prevent premature recruitment of ribosome-associated factors active during translation.